Analisis Frasa Verba dan Frasa Nomina dalam Teks Argumentasi pada Buku Ajar Kelas XI SMA Kurikulum Merdeka - Itsnaini Nur Khasanah; Dea Sheva Dwi Anggraeni; Kholifatun Nisya; Rossa Farhana Ridho Susanti; Asep Purwo Yudi Utomo; Uki Hares Yulianti (Pusat Riset dan Inovasi Nasional, 2023)
This research analyzed one of the syntactic fields of study, namely phrases in argumentation texts in class XI textbooks of the Kurikulum Merdeka. Two data will be studied in argumentation texts entitled